An introduction to multicultural education - Banks, James A. (Pearson/Allyn and Bacon, 2008)
This book gives teachers a strong background in the conceptual, theoretical, and philosophical issues in multicultural education. Cultural Diversity and Education is designed to help pre-service and in-service educators clarify the philosophical and definitional issues related to pluralistic education, derive a clarified philosophical position, design and implement effective teaching strategies that reflect ethnic and cultural diversity, and prepare sound guidelines for multicultural programs and practices. This book describes actions that educators can take to institutionalize educational programs and practices related to ethnic and cultural diversity.